ON THE CONCEPT OF IMPROVEMENT OF TAX LEGISLATION OF THE REPUBLIC OF KAZAKHSTAN (Journal of actual problems of jurisprudence, 2024)
The relevance of this study is conditioned by the need to revise the strategy of financial support for the development of the state, especially in the context of improving the tax legislation. The purpose of this study was to examine and analyse the problematic aspects of the tax system in Kazakhstan to identify promising ways to improve it, considering international practices, specifically of Poland. The methods of statistical analysis, analogy, and generalisation, as well as formal legal and formal logical approaches were used in the study. The study covered the features of the evolution of the legal formation of the tax system in Kazakhstan, as well as the problems inherent in the current stage of its functioning. It was emphasised that the formation of the institutional structure of the tax system of the state is inextricably linked with the choice of tax policy guidelines and its subsequent implementation. It was argued that a well-organised and efficient tax system is characterised by its ability to adapt to variable environmental conditions and factors. This requires regular assessment of the functioning of the tax system and comparing it with analogous systems in other countries. Particular attention was directed towards the comparative legal analysis of the tax system of Kazakhstan with other countries – Poland. As a result, promising ways to improve the tax system of Kazakhstan were highlighted. The study also analysed the existing opinions and concepts of scholars on the subject. The investigation of different opinions helped to comprehend the complexity of this phenomenon and possible solutions for the improvement of the tax system of Kazakhstan in modern realities. The results of this study may be valuable for the development of effective methodologies for the detection of offences in this area. Furthermore, they may serve as a basis for recommendations and amendments to the current legislation of the Republic of Kazakhstan.Keywords: financial system, world practices, evolution of legal regulation, tax legislation of Kazakhstan, ways of digitalisation.